KEPEMIMPINAN TRANSFORMASIONAL DALAM MEMBANGUN BUDAYA DISIPLIN GURU DI SEKOLAH ISLAM TERPADU QURROTA A’YUN - Ryan Juppenny; Sulton Sulton (EDUPEDIA, 2026)
This study aims to analyze the transformational leadership strategies of school principals in building a culture of discipline and work ethic among teachers at SDIT Qurrota A’yun Ponorogo. The research focuses on the relationship between leadership practices, managerial systems, school organizational climate, and the internalization of moral and professional values within the context of an integrated Islamic school. The research subjects include the principal, teachers, and internal school documents related to teacher discipline and performance. This study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, non-participant observation, and document analysis, and analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing. The findings indicate that teacher discipline and work ethic have not been evenly established as a collective organizational culture. While some teachers demonstrate high levels of discipline and professional responsibility, others show inconsistent work behavior. The results reveal that the principal’s leadership tends to be administrative rather than fully transformational, particularly in terms of inspirational motivation, individualized consideration, and value internalization. This study concludes that strengthening a culture of discipline in Islamic schools requires the integration of transformational leadership practices with the reinforcement of moral values such as amanah and itqan as the foundation of professional work ethics. These findings contribute theoretically and practically to the development of a holistic and value-based model of Islamic school leadership.